Periapical radiographs overestimate root canal wall thickness during post space preparation - Souza, E. M. [UNESP]; Bretas, R. T.; Cenci, M. S.; Maia-Filho, E. M.; Bonetti-Filho, I. [UNESP] (Wiley-Blackwell, 2008)
Aim To evaluate differences between anatomic and radiographic measurements of root canal wall thickness (RCWT) after each root canal preparation stage during post placement.Methodology Twenty mandibular premolars with a single canal were decoronated and the roots embedded in resin using a teflon muffle. Roots were sectioned horizontally at a pre-established level and canals were prepared for post placement. Endodontic hand files were used for root canal preparation, followed by Gates Glidden drills and Peeso reamers. Standardized radiographs and photographs at pre-established measurement levels were taken before preparation, after root canal instrumentation, after Gates Glidden preparation and after Peeso enlargement. All images were digitized and RCWT at the mesial and distal walls measured (IMAGETOOL 3.0). Differences between radiographic and anatomic measurements were analysed with paired t-tests. ANOVA was used to compare the percentages of radiographic distortions.Results Regardless of the time-point evaluated, RCWT determined by radiographs were greater than the respective anatomic measurements (P < 0.05). The difference detected at each stage was similar and constant (P > 0.05).Conclusions Throughout preparation for post placement, radiographic images overestimated the RCWT by approximately 25%, regardless of the clinical stage evaluated.
Keywords: post preparation; radiographic images; root canal wall thickness